Electrical characterization of 0.13℗æm CMOS transistor using TSUPREM-4 and MEDICI - Rusnita Rafee
This final year project is about the use of Synopsys' Taurus TCAD (TSUPREM-4 and PMOS transistor).This project also includes how the process simulation by TSUPREM-4 to produce an output file containing complete structure, mesh and doping information that can be read into MEDICI device simulator to extract electrical characteristics.